2022
DOI: 10.3389/fped.2022.865441
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics, Laboratory Findings, Management, and Outcome of Severe Coronavirus Disease 2019 in Children at a Tertiary Care Center in Riyadh, Saudi Arabia: A Retrospective Study

Abstract: BackgroundNumerous studies worldwide have reported COVID-19 in children; however, the clinical symptoms and consequences of COVID-19 in children have only been reported in a few studies in Saudi and gulf region. Therefore, we aimed to investigate the clinical features and outcomes of COVID-19 infection in children and the therapeutic interventions used.MethodsThis retrospective cohort study included 96 patients with confirmed severe acute respiratory syndrome coronavirus 2 infection aged ≤14 years who were adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
(60 reference statements)
0
0
0
Order By: Relevance
“…The most common clinical presentation is fever, cough, sore throat, headache, nausea, vomiting, diarrhea, breathlessness, fatigue, malaise, or croup [3,4]. In a retrospective study from Saudi Arabia, fever and respiratory symptoms were reported as the most common clinical characteristics of COVID-19 in children [5]. Also, a survey conducted in northern Sierra Leone stated that most children were asymptomatic.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…The most common clinical presentation is fever, cough, sore throat, headache, nausea, vomiting, diarrhea, breathlessness, fatigue, malaise, or croup [3,4]. In a retrospective study from Saudi Arabia, fever and respiratory symptoms were reported as the most common clinical characteristics of COVID-19 in children [5]. Also, a survey conducted in northern Sierra Leone stated that most children were asymptomatic.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…The most common clinical presentation is fever, cough, sore throat, headache, nausea, vomiting, diarrhea, breathlessness, fatigue, malaise, or croup [3,4]. In a retrospective study from Saudi Arabia, fever and respiratory symptoms were reported as the most common clinical characteristics of COVID-19 in children [5]. Also, a survey conducted in northern Sierra Leone stated that most children were asymptomatic.…”
Section: Clinical Presentationmentioning
confidence: 99%